If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 2x + -2y = 3 Solving 2x + -2y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 2x + -2y + 2y = 3 + 2y Combine like terms: -2y + 2y = 0 2x + 0 = 3 + 2y 2x = 3 + 2y Divide each side by '2'. x = 1.5 + y Simplifying x = 1.5 + y

| -10v+2=-70 | | -3y-10=6y+17 | | y=-20sin(4x) | | 49x=245 | | 7k=k-18 | | -4(8+5)=8 | | x-2x=3x-27 | | 6t=48 | | 2x+3=2y | | 5y-3=5(y-1) | | x^2+6x-21=0 | | 3x^2-16x=x^2-30 | | 0.30x+0.25(30)=0.15(106) | | 4x-y=21 | | 9p^2+6p-8=0 | | 5y-10=7(2y-3)+14-9y | | 6(n+7)=2(21+3n) | | x/6+5=x/6 | | 12x^2+11x-5=0 | | 5x^2-16=-x^2+80 | | 0=(21x)(21x)-2x-40 | | 11x^2+x-2=0 | | 3/4(x-7)=x+2 | | X^2+2x-324=2x | | 7+9(x-8)=10-3(x-5) | | 3(x-5)=2(x+2) | | 9x-3=9(x-2) | | X^2+10=2 | | r=4k+4w | | -4y+6=-2(4y+5) | | 7(6x+4)+2=42x+30 | | -9(t-8)-(t+8)=3 | | -3(t-3)+9t=4t-1 | | 3g-12=9 | | 2/3(x-8)=x+2 | | 0.5x-4.8=-2.3 | | -x^2-10x=25 | | 8y+3(y-7)=3(y+2)-4 | | -3(3s-5)-15=-3(7s+1)-5 | | X^2+2=3 | | 4d=27 | | 6x-15x+-5=58 | | 7-4w=-10 | | 0.25n+0.1=9.8 | | 5(92-5x)=27 | | 0.4(x+20)-0.8X=44 | | 2(2+4)= | | 18m+30=66 | | -1.66x+.66=-11 | | 4(x-2)+6=6x-2(2+x) | | -7x+8=-20 | | 2(x-5)=4x-2(x-5) | | 0.2-0.01(x+2)=-0.03(2-x) | | 8n-6=9n | | 6x^2+2x-9=0 | | 42=6-9h | | 8(x+3)=5(k-3) | | -10=10w-20 | | 8x^2-370=0 | | 0=-16t^2+38.8t+3 | | 32-2x=20 | | 3r=-21 | | 139=3d+2(4d+9) | | Y=x^2-17x+50 | | -12.5+0.5p=0.9p+5.3 |